Skin Microbiome in Atopic Dermatitis - Edslev, S; Agner, T; Andersen, P (Acta dermato-venereologica, 2020)
Atopic dermatitis is a common inflammatory skin disease with a complex pathogenesis that includes imbalanced immune system signalling, impaired skin barrier and enhanced Staphylococcus aureus skin colonization. The skin bacterial communities are characterized by increasing abundance of S. aureus, leading to reduced diversity compared with the bacterial communities on healthy skin, and increasing disease severity. In contrast, fungal communities are richer and more diverse on the skin of patients with atopic dermatitis, although distribution of the most common species is similar in patients and controls. Filaggrin deficiency in atopic dermatitis skin might be related to the enhanced skin colonization by S. aureus. In addition, S. aureus expressing variant virulence factors have been shown to elicit atopic dermatitis-like phenotypes in mice, indicating that specific S. aureus strains can induce flare-ups. This review aims to provide an overview of the recent literature on the skin microbiome in atopic dermatitis.